Pathological and immunological features of canine necrotising meningoencephalitis and granulomatous meningoencephalitis - Uchida, Kazuyuki; Park, Eunsil; Tsuboi, Masaya; Chambers, James K.; Nakayama, Hiroyuki (The Veterinary Journal, 2016)
•Necrotising meningoencephalitis (NME) can be divided into cortex dominant and white matter dominant types.•Lesions in granulomatous meningoencephalitis (GME) are characterised by granulomas with infiltration by T lymphocytes.•Autoantibodies against astrocytes are detected predominantly in NME.•Different cytokine and chemokine responses are seen in NME and GME. Necrotising meningoencephalitis (NME) and granulomatous meningoencephalitis (GME) are idiopathic inflammatory diseases of the canine central nervous system (CNS). Typical NME occurs predominantly in small breeds of dogs, such as Pug, Maltese and Yorkshire terriers. Although there is no specific breed predisposition to GME, toy and terrier breeds appear to be overrepresented. Recent molecular investigations have identified genetic risk factors for NME in Pug, Maltese and other toy breed dogs; however, details of the pathogenesis of this disease remain to be clarified. NME is characterised pathologically by necrotic lesions with mononuclear cell infiltration in the meninges and perivascular spaces. On the basis of the distribution pattern of major necrotic foci, NME can be divided into cortex dominant and white matter dominant types; the latter is designated necrotising leucoencephalitis (NLE). Lesions in GME are characterised by the accumulation of lymphocytes and macrophages with epithelioid morphology, forming granulomas around blood vessels. Some common genetic factors and/or some additional triggers, such as infection or vaccination, may play a role in the pathogenesis of NME, NLE and GME; however, the host immune responses may define the pathological phenotypes. Different cytokine and chemokine responses are seen in NME, NLE and GME, whilst autoantibodies against astrocytes are detected predominantly in NME. This review focuses on the pathological and immunological characteristics of these canine idiopathic inflammatory CNS disorders.